Experiencing spaces and places through human senses with the presence of nature - Darine T. Zacca (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The theory of “Percept, Affect, Concept” by Gilles Deleuze & Félix Guattari will be the methodology for discovering the impact and the presence of nature on experiencing spaces, in some chosen iconic architectures such as “Villa Savoye” by Le Corbusier, “Fallingwater” by Frank Lloyd Wright and “Swiss Soundbox” by Peter Zumthor, ranging from modern to contemporary architectures. How can the presence of nature lead to a multisensory unique experience of Space? A committed, integrated, or convoked nature will form the main topic of the architectural multisensory experience of spaces, atmospheres, experiences, and memories of a place, of what was learned, of what was lived, and memories of places as well as “Genius Loci”, to have such a unique experience.